Peran Pendidikan Karakter dalam Membentuk Sikap Kewirausahaan Siswa Sekolah Dasar - Tafana Dwi Ismiyati; Rohma Dini Aulia; Oman Farhurahman (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This study aims to understand the role of character education in the formation of entrepreneurial attitudes in elementary school students. Character education is considered an important foundation for developing entrepreneurial skills, such as independence, creativity, hard work, and the courage to take risks. The method used in this study is descriptive-qualitative through literature studies, analyzing various relevant sources regarding the implementation of entrepreneurship education at the elementary school level. The findings of the study indicate that character education can be effective in forming entrepreneurial attitudes in students if implemented through integration into subjects, personal development activities, extracurricular programs and local content. By consistently applying character values, students can develop self-confidence, responsibility, and innovative mindsets that support them to become entrepreneurs in the future. This study provides recommendations for educators and policy makers to design comprehensive and applicable education programs to instill entrepreneurial character from an early age.